Prevalence of Dysmenorrhea in University Students in Turkey: Effect on Daily Activities and Evaluation of Different Pain Management Methods - POTUR, DİLEK (ELSEVIER SCIENCE INC, 2014)
This study was conducted to determine the following among a group of female university students: the prevalence of dysmenorrhea; pain severity ratings; methods used to manage dysmenorrhea; and the effect of dysmenorrhea on daily activities, school attendance, and ability to communicate with friends. This cross-sectional study was conducted between December 2009 and February 2010 at a public university located in Istanbul, in the northwest area of Turkey. The study group included 1515 female students. Data were collected from the female students in the study group using a self-report questionnaire; the severity of dysmenorrhea was determined with the visual analog scale. The data were examined with mean, percentages, chi-square analysis, and logistic regression. The prevalence of dysmenorrhea in the study group was 85.7%. Of this group of subjects with dysmenorrhea, 30.4% described their menstrual pain as severe, 49.8% as moderate, and 19.8% as mild. The mean severity of pain among the students was 6.33 +/- 2.32 on the VAS. The majority of participants who experienced moderate or severe pain regularly used analgesics for pain management, and participants who experienced severe pain used analgesics before the beginning of menstruation. Participants who experienced moderate pain used herbal tea, massage, heat application, rest, and distraction for pain management. Participants who experienced severe pain consulted a physician and that a significant difference existed between the dysmenorrhea rating groups in this regard (p < .001). Severe pain was significantly associated with school absenteeism and limitations in social activities/functioning (p < .001). Dysmenorrhea is highly prevalent among university students and is related to school absenteeism, ability to participate in and enjoy daily activities, and limitations in social activities/functioning. (C) 2014 by the American Society for Pain Management Nursing
Keywords: MENSTRUAL PAIN; ADOLESCENTS; IMPACT; ASSOCIATION; DISCOMFORT; WOMEN